KEBIJAKAN PEMBANGUNAN KESATUAN PENGELOLAAN HUTAN DI INDONESIA: SUATU TEROBOSAN DALAM MENCIPTAKAN PENGELOLAAN HUTAN LESTARI - Atika Rahmadanty; I Gusti Ayu Ketut Rachmi Handayani; Fatma Ulfatun Najicha (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The purpose of this study is to find out why forest management through the development policy of the Forest Management Unit in Indonesia is needed and how the challenges of building a Forest Management Unit in the implementation of forestry in Indonesia. This study uses normative research methods with data sources in the form of primary and secondary legal materials. The results showed that the development policy of the Forest Management Unit is needed for the benefit of community development in optimizing the management and utilization of potential funding for climate management of the regional forestry sector either at the provincial, district / city level or management unit level as well as challenges in the implementation of forests in Indonesia including limitations of professional human resources (HR), support of local governments that are not optimal, the disharmony of relationships, social conflicts and economic interests.